Islamic Republic of Mauritania : 2006 Article IV Consultation-Staff Report; Staff Statement; Public Information Notice and Press Release on the Executive Board Discussion; and Statement by the Executive Director for the Islamic Republic of Mauritania. (IMF Staff Country Reports; Country Report ;, 2006)
Mauritania achieved substantial progress owing to its macroeconomic policies, budget formulation, governance, and transparency under the economic program. Executive Directors commended the program and emphasized the need for tight fiscal and monetary policies. Directors noted the implementation of all remedial actions and agreed that Mauritania qualifies for debt relief under the Multilateral Debt Relief Initiative (MDRI). They also called on the authorities to strengthen the financial sector regulatory framework, and commended the comprehensive Anti-Money Laundering and Combating the Financing of Terrorism framework.